Vous êtes sur la page 1sur 12

Appendix B

Complex Numbers

The ability to manipulate complex numbers is very handy in circuit anal-


ysis and in electrical engineering in general. Complex numbers are par-
ticularly useful in the analysis of ac circuits. Again, although calculators
and computer software packages are now available to manipulate com-
plex numbers, it is still advisable for a student to be familiar with how to
handle them by hand.
B.1 Representations of Complex Numbers
A complex number z may be written in rectangular form as
z = x + jy (B.1)

where j = −1; x is the real part of z while y is the imaginary part of
z; that is,
x = Re(z), y = Im(z) (B.2)

√ number z is shown plotted in the complex plane in Fig. B.1.


The complex The complex plane looks like the two-dimen-
Since j = −1, sional curvilinear coordinate space, but it is not.
1
= −j
j
Im
j 2 = −1 jy
z

j 3 = j · j 2 = −j r
(B.3) y
j4 = j2 · j2 = 1 u
j5 = j · j4 = j
0 x Re
..
.
Figure B.1 Graphical representation
j n+4 = j n of a complex number.
A second way of representing the complex number z is by speci-
fying its magnitude r and the angle θ it makes with the real axis, as Fig.
B.1 shows. This is known as the polar form. It is given by
z = |z| θ = r θ (B.4)

where  y
r= x2 + y2, θ = tan−1 (B.5a)
x
or
x = r cos θ, y = r sin θ (B.5b)

that is,
z = x + jy = r θ = r cos θ + j r sin θ (B.6)

In converting from rectangular to polar form using Eq. (B.5), we must


exercise care in determining the correct value of θ. These are the four
possibilities:
y
z = x + jy, θ = tan−1 (1st Quadrant)
x
y
z = −x + jy, θ = 180◦ − tan−1 (2nd Quadrant)
x

851

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
852 APPENDIX B Complex Numbers

y
z = −x − jy, θ = 180◦ + tan−1 (3rd Quadrant)
x
(B.7)
y
z = x − jy, θ = 360◦ − tan−1 (4th Quadrant)
x
assuming that x and y are positive.
In the exponential form, z = re j θ so that dz/dθ = The third way of representing the complex z is the exponential form:
jre j θ = jz.
z = rej θ (B.8)

This is almost the same as the polar form, because we use the same
magnitude r and the angle θ.
The three forms of representing a complex number are summarized
as follows.

z = x + jy, (x = r cos θ, y = r sin θ) Rectangular form


  y 
z = r θ, r = x 2 + y 2 , θ = tan−1 Polar form
x
  y
z = rej θ , r = x 2 + y 2 , θ = tan−1 Exponential form
x
(B.9)

The first two forms are related by Eqs. (B.5) and (B.6). In Section B.3
we will derive Euler’s formula, which proves that the third form is also
equivalent to the first two.

E X A M P L E B . 1
Express the following complex numbers in polar and exponential form:
(a) z1 = 6 + j 8, (b) z2 = 6 − j 8, (c) z3 = −6 + j 8, (d) z4 = −6 − j 8.
Solution:
Notice that we have deliberately chosen these complex numbers to fall in
Im the four quadrants, as shown in Fig. B.2.
z3 z1
j8 (a) For z1 = 6 + j 8 (1st quadrant),
j6  8
r3 j4 r1 r1 = 62 + 82 = 10, θ1 = tan−1 = 53.13◦
u3 6
j2 u1 ◦
u4 Hence, the polar form is 10 53.13◦ and the exponential form is 10ej 53.13 .
(b) For z2 = 6 − j 8 (4th quadrant),
−8 −6 −4 −2 0 2 4 6 8 Re
−j2 u2  8
r2 = 62 + (−8)2 = 10, θ2 = 360◦ − tan−1 = 306.87◦
r4 −j4 r2 6
−j6 so that the polar form is 10 306.87◦ and the exponential form is

z4 −j8 z2 10ej 306.87 . The angle θ2 may also be taken as −53.13◦ , as shown in
Fig. B.2, so that the polar form becomes 10 − 53.13◦ and the exponen-

Figure B.2 For Example B.1. tial form becomes 10e−j 53.13 .
(c) For z3 = −6 + j 8 (2nd quadrant),
 8
r3 = (−6)2 + 82 = 10, θ3 = 180◦ − tan−1 = 126.87◦
6

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
APPENDIX B Complex Numbers 853

Hence, the polar form is 10 126.87◦ and the exponential form is



10ej 126.87 .
(d) For z4 = −6 − j 8 (3rd quadrant),
 8
r4 = (−6)2 + (−8)2 = 10, θ4 = 180◦ + tan−1 = 233.13◦
6
so that the polar form is 10 233.13◦ and the exponential form is

10ej 233.13 .

PRACTICE PROBLEM B.1


Convert the following complex numbers to polar and exponential forms:
(a) z1 = 3 − j 4, (b) z2 = 5 + j 12, (c) z3 = −3 − j 9, (d) z4 = −7 + j .
◦ ◦
Answer: (a) 5 306.9◦ , 5ej 306.9 , (b) 13 67.38◦ , 13ej 67.38 ,
◦ ◦
(c) 9.487 251.6◦ , 9.487ej 251.6 , (d) 7.071 171.9◦ , 7.071ej 171.9 .

E X A M P L E B . 2
Convert the following complex numbers into rectangular form:

(a) 12 − 60◦ , (b) −50 285◦ , (c) 8ej 10 , (d) 20e−j π/3 .
Solution:
(a) Using Eq. (B.6),

12 − 60◦ = 12 cos(−60◦ ) + j 12 sin(−60◦ ) = 6 − j 10.39

Note that θ = −60◦ is the same as θ = 360◦ − 60◦ = 300◦ .


(b) We can write

−50 285◦ = −50 cos 285◦ − j 50 sin 285◦ = −12.94 + j 48.3

(c) Similarly,

8ej 10 = 8 cos 10◦ + j 8 sin 10◦ = 7.878 + j 1.389

(d) Finally,

20e−j π/3 = 20 cos(−π/3) + j 20 sin(−π/3) = 10 − j 17.32

PRACTICE PROBLEM B.2


Find the rectangular form of the following complex numbers:

(a) −8 210◦ , (b) 40 305◦ , (c) 10e−j 30 , (d) 50ej π/2 .
Answer: (a) 6.928 + j 4, (b) 22.94 − j 32.77, (c) 8.66 − j 5, (d) j 50.

B.2 Mathematical Operations


Two complex numbers z1 = x1 + jy1 and z2 = x2 + jy2 are equal if and We have used lightface notation for complex
only if their real parts are equal and their imaginary parts are equal, numbers—since they are not time- or frequency-
dependent—whereas we use boldface notation
x1 = x2 , y1 = y2 (B.10) for phasors.

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
854 APPENDIX B Complex Numbers

The complex conjugate of the complex number z = x + jy is

z∗ = x − jy = r − θ = re−j θ (B.11)

Thus the complex conjugate of a complex number is found by replacing


every j by −j .
Given two complex numbers z1 = x1 + jy1 = r1 θ1 and z2 =
x2 + jy2 = r2 θ2 , their sum is

z1 + z2 = (x1 + x2 ) + j (y1 + y2 ) (B.12)

and their difference is

z1 − z2 = (x1 − x2 ) + j (y1 − y2 ) (B.13)

While it is more convenient to perform addition and subtraction of


complex numbers in rectangular form, the product and quotient of the
two complex numbers are best done in polar or exponential form. For
their product,
z1 z2 = r1 r2 θ1 + θ2 (B.14)

Alternatively, using the rectangular form,

z1 z2 = (x1 + jy1 )(x2 + jy2 )


(B.15)
= (x1 x2 − y1 y2 ) + j (x1 y2 + x2 y1 )

For their quotient,


z1 r1
= θ1 − θ 2 (B.16)
z2 r2
Alternatively, using the rectangular form,
z1 x1 + jy1
= (B.17)
z2 x2 + jy2
We rationalize the denominator by multiplying both the numerator and
denominator by z2∗ .

z1 (x1 + jy1 )(x2 − jy2 ) x1 x2 + y1 y2 x2 y1 − x1 y2


= = +j (B.18)
z2 (x2 + jy2 )(x2 − jy2 ) x2 + y2
2 2
x22 + y22

E X A M P L E B . 3
If A = 2 + j 5, B = 4 − j 6, find: (a) A∗ (A + B), (b) (A + B)/(A − B).
Solution:
(a) If A = 2 + j 5, then A∗ = 2 − j 5 and

A + B = (2 + 4) + j (5 − 6) = 6 − j

so that

A∗ (A + B) = (2 − j 5)(6 − j ) = 12 − j 2 − j 30 − 5 = 7 − j 32

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
APPENDIX B Complex Numbers 855

(b) Similarly,

A − B = (2 − 4) + j (5 − −6) = −2 + j 11

Hence,

A+B 6−j (6 − j )(−2 − j 11)


= =
A−B −2 + j 11 (−2 + j 11)(−2 − j 11)
−12 − j 66 + j 2 − 11 −23 − j 64
= = = −0.184 − j 0.512
(−2) + 11
2 2 125

PRACTICE PROBLEM B.3


Given that C = −3 + j 7 and D = 8 + j , calculate:
(a) (C − D ∗ )(C + D ∗ ), (b) D 2 /C ∗ , (c) 2CD/(C + D).
Answer: (a) −103 − j 26, (b) −5.19 + j 6.776, (c) 6.054 + j 11.53.

E X A M P L E B . 4
Evaluate:

(2 + j 5)(8ej 10 ) j (3 − j 4)∗
(a) (b)
2 + j 4 + 2 − 40◦ (−1 + j 6)(2 + j )2
Solution:
(a) Since there are terms in polar and exponential forms, it may be best
to express all terms in polar form:

2 + j5 = 22 + 52 tan−1 5/2 = 5.385 68.2◦

(2 + j 5)(8ej 10 ) = (5.385 68.2◦ )(8 10◦ ) = 43.08 78.2◦
2 + j4 + 2 − 40◦ = 2 + j 4 + 2 cos(−40◦ ) + j 2 sin(−40◦ )
= 3.532 + j 2.714 = 4.454 37.54◦

Thus,

43.08 78.2◦

(2 + j 5)(8ej 10 )
= = 9.672 40.66◦
2 + j4 + 2 − 40◦ 4.454 37.54◦

(b) We can evaluate this in rectangular form, since all terms are in that
form. But

j (3 − j 4)∗ = j (3 + j 4) = −4 + j 3
(2 + j )2 = 4 + j 4 − 1 = 3 + j 4
(−1 + j 6)(2 + j )2 = (−1 + j 6)(3 + j 4) = −3 − 4j + j 18 − 24
= −27 + j 14

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
856 APPENDIX B Complex Numbers

Hence,
j (3 − j 4)∗ −4 + j 3 (−4 + j 3)(−27 − j 14)
= =
(−1 + j 6)(2 + j ) 2 −27 + j 14 272 + 142
108 + j 56 − j 81 + 42
= = 0.1622 − j 0.027
925

PRACTICE PROBLEM B.4


Evaluate these complex fractions:
 ∗
6 30◦ + j 5 − 3 (15 − j 7)(3 + j 2)∗
(a) (b)
−1 + j + 2ej 45◦ (4 + j 6)∗ (3 70◦ )

Answer: (a) 1.213 237.4◦ , (b) 2.759 − 287.6◦ .

B.3 Euler’s Formula


Euler’s formula is an important result in complex variables. We derive it
from the series expansion of ex , cos θ , and sin θ . We know that

x2 x3 x4
ex = 1 + x + + + + ··· (B.19)
2! 3! 4!
Replacing x by j θ gives

θ2 θ3 θ4
ej θ = 1 + j θ − −j + + ··· (B.20)
2! 3! 4!
Also,
θ2 θ4 θ6
cos θ = 1 − + − + ···
2! 4! 6!
(B.21)
θ3 θ5 θ7
sin θ = θ − + − + ···
3! 5! 7!
so that
θ2 θ3 θ4 θ5
cos θ + j sin θ = 1 + j θ − −j + +j − ··· (B.22)
2! 3! 4! 5!
Comparing Eqs. (B.20) and (B.22), we conclude that

ej θ = cos θ + j sin θ (B.23)

This is known as Euler’s formula. The exponential form of representing


a complex number as in Eq. (B.8) is based on Euler’s formula. From Eq.
(B.23), notice that

cos θ = Re(ej θ ), sin θ = Im(ej θ ) (B.24)

and that 
|ej θ | = cos2 θ + sin2 θ = 1

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
APPENDIX B Complex Numbers 857

Replacing θ by −θ in Eq. (B.23) gives

e−j θ = cos θ − j sin θ (B.25)

Adding Eqs. (B.23) and (B.25) yields

1 jθ
cos θ = (e + e−j θ ) (B.26)
2

Substracting Eq. (B.24) from Eq. (B.23) yields

1 jθ
sin θ = (e − e−j θ ) (B.27)
2j

B.4 Useful Identities


The following identities are useful in dealing with complex numbers. If
z = x + jy = r θ , then

zz∗ = x 2 + y 2 = r 2 (B.28)
√  √ √
z = x + jy = rej θ/2 = r θ/2 (B.29)

zn = (x + jy)n = r n nθ = r n ej θ = r n (cos nθ + j sin nθ ) (B.30)

z1/n = (x + jy)1/n = r 1/n θ/n + 2π k/n


(B.31)
k = 0, 1, 2, . . . , n − 1
ln(rej θ ) = ln r + ln ej θ = ln r + j θ + j 2kπ
(B.32)
(k = integer)
1
= −j
j
e±j π = −1
(B.33)
e±j 2π = 1
ej π/2 = j
e−j π/2 = −j
Re(e(α+j ω)t ) = Re(eαt ej ωt ) = eαt cos ωt
(B.34)
Im(e(α+j ω)t ) = Im(eαt ej ωt ) = eαt sin ωt

E X A M P L E B . 5

If A = 6 + j 8, find: (a) A, (b) A4 .
Solution:
(a) First, convert A to polar form:
 8
r= 62 + 82 = 10, θ = tan−1 = 53.13◦ , A = 10 53.13◦
6
Then √ √
A= 10 53.13◦ /2 = 3.162 26.56◦

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
858 APPENDIX B Complex Numbers

(b) Since A = 10 53.13◦ ,

A4 = r 4 4θ = 104 4 × 53.13◦ = 10,000 212.52◦

PRACTICE PROBLEM B.5


If A = 3 − j 4, find: (a) A1/3 (3 roots), and (b) ln A.
Answer: (a) 1.71 102.3◦ , 1.71 222.3◦ , 1.71 342.3◦ ,
(b) 1.609 + j 5.356.

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
Appendix C
Mathematical Formulas

This appendix—by no means exhaustive—serves as a handy reference.


It does contain all the formulas needed to solve circuit problems in this
book.
C.1 Quadratic Formula
The roots of the quadratic equation ax 2 + bx + c = 0 are

−b ± b2 − 4ac
x1 , x2 =
2a
C.2 Trigonometric Identities

sin(−x) = − sin x
cos(−x) = cos x
1 1
sec x = , csc x =
cos x sin x
sin x 1
tan x = , cot x =
cos x tan x
sin(x ± 90◦ ) = ± cos x
cos(x ± 90◦ ) = ∓ sin x
sin(x ± 180◦ ) = − sin x
cos(x ± 180◦ ) = − cos x
cos2 x + sin2 x = 1
a b c
= = (law of sines)
sin A sin B sin C
a = b + c − 2bc cos A
2 2 2
(law of cosines)
tan 1
(A − B) a−b
2
= (law of tangents)
tan 1
2
(A + B) a+b

sin(x ± y) = sin x cos y ± cos x sin y


cos(x ± y) = cos x cos y ∓ sin x sin y
tan x ± tan y
tan(x ± y) =
1 ∓ tan x tan y
2 sin x sin y = cos(x − y) − cos(x + y)
2 sin x cos y = sin(x + y) + sin(x − y)
2 cos x cos y = cos(x + y) + cos(x − y)
sin 2x = 2 sin x cos x

859

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
860 APPENDIX C Mathematical Formulas

cos 2x = cos2 x − sin2 x = 2 cos2 x − 1 = 1 − 2 sin2 x


2 tan x
tan 2x =
1 − tan2 x
1
sin2 x = (1 − cos 2x)
2
1
cos2 x = (1 + cos 2x)
2
 
−K2
K1 cos x + K2 sin x = K12 + K22 cos x + tan−1
K1
ej x = cos x + j sin x (Euler’s formula)
ej x + e−j x
cos x =
2
e − e−j x
jx
sin x =
2j
1 rad = 57.296◦
C.3 Hyperbolic Functions

1 x
sinh x = (e − e−x )
2
1 x
cosh x = (e + e−x )
2
sinh x
tanh x =
cosh x
1
coth x =
tanh x
1
csch x =
sinh x
1
sech x =
cosh x
sinh(x ± y) = sinh x cosh y ± cosh x sinh y
cosh(x ± y) = cosh x cosh y ± sinh x sinh y

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
APPENDIX C Mathematical Formulas 861

C.4 Derivatives
If U = U (x), V = V (x), and a = constant,
d dU
(aU ) = a
dx dx
d dV dU
(U V ) = U +V
dx dx dx
 dU dV
d U V −U
= dx dx
dx V V2
d
(aU n ) = naU n−1
dx
d U dU
(a ) = a U ln a
dx dx
d U dU
(e ) = eU
dx dx
d dU
(sin U ) = cos U
dx dx
d dU
(cos U ) = − sin U
dx dx
C.5 Indefinite Integrals
If U = U (x), V = V (x), and a = constant,

a dx = ax + C

U dV = U V − V dU (integration by parts)

U n+1
U n dU = + C, n = 1
n+1

dU
= ln U + C
U

aU
a U dU = + C, a > 0, a = 1
ln a

1 ax
eax dx = e +C
a

eax
xeax dx = (ax − 1) + C
a2

eax 2 2
x 2 eax dx = (a x − 2ax + 2) + C
a3

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents
862 APPENDIX C Mathematical Formulas

ln x dx = x ln x − x + C

1
sin ax dx = − cos ax + C
a

1
cos ax dx = sin ax + C
a

x sin 2ax
sin2 ax dx = − +C
2 4a

x sin 2ax
cos2 ax dx = + +C
2 4a

1
x sin ax dx = (sin ax − ax cos ax) + C
a2

1
x cos ax dx = (cos ax + ax sin ax) + C
a2

1
x 2 sin ax dx = (2ax sin ax + 2 cos ax − a 2 x 2 cos ax) + C
a3

1
x 2 cos ax dx = (2ax cos ax − 2 sin ax + a 2 x 2 sin ax) + C
a3

eax
eax sin bx dx = (a sin bx − b cos bx) + C
a2 + b2

eax
eax cos bx dx = (a cos bx + b sin bx) + C
a 2 + b2

sin(a − b)x sin(a + b)x


sin ax sin bx dx = − + C, a 2 = b2
2(a − b) 2(a + b)

cos(a − b)x cos(a + b)x


sin ax cos bx dx = − − + C, a 2 = b2
2(a − b) 2(a + b)

sin(a − b)x sin(a + b)x


cos ax cos bx dx = + + C, a 2 = b2
2(a − b) 2(a + b)

dx 1 x
= tan−1 + C
a2 +x 2 a a

x 2 dx x
= x − a tan−1 + C
a +x
2 2 a


dx 1 x 1 −1 x
= 2 + tan +C
(a 2 + x 2 )2 2a x 2 + a2 a a

| | e-Text Main Menu | Textbook Table of Contents | Problem Solving Workbook Contents